Gmelina arborea - Lamb, A (Commenwealth Forestry Institute, University of Oxford, 1968)
As a result of the greater interest during recent years in plantations of fast growing trees within the lowland tropical zone, Gmelina is now on trial in a great many countries. There are few countries however where it has been tried for long enough and on a large enough scale to assess its potentialities and limitations. Streets (1962) summarised experience up to 1962, giving most detail for Nigeria and Sierra Leone where commercial plantations have been made. It promises to be an important species in Malawi and Malaya but less so in the sub-tropical climates of Rhodesia and Zambia. Recently detailed timber and pulp tests have revealed its many valuable properties and stimulated interest in large scale plantations...